The Role of FoxG1 in the Inner Ear - Ding, Yanyan; Meng, Wei; Kong, Weijia; He, Zuhong; Chai, Renjie (Frontiers in Cell and Developmental Biology, 2020)
Sensorineural deafness is mainly caused by damage to the tissues of the inner ear, and hearing impairment has become an increasingly serious global health problem. When the inner ear is abnormally developed or is damaged by inflammation, ototoxic drugs, or blood supply disorders, auditory signal transmission is inhibited resulting in hearing loss. FoxG1 is an important nuclear transcriptional regulator, which is related to the differentiation, proliferation, development, and survival of cells in the brain, telencephalon, inner ear, and other tissues. Previous studies have shown that when FoxG1 is abnormally expressed, the development and function of inner ear hair cells is impaired. This review discusses the role and regulatory mechanism of FoxG1 in inner ear tissue from various aspects – such as the effect on inner ear development, the maintenance of inner ear structure and function, and its role in the inner ear when subjected to various stimulations or injuries – in order to explain the potential significance of FoxG1 as a new target for the treatment of hearing loss.